PERAN AKTIF DAN PARTISIPASI KELOMPOK TANI DALAM IMPLEMENTASI INOVASI TEKNOLOGI PADI SPESIFIK LOKASI - Roosganda Elizabeth (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The active role and participation of farmer groups is important as a forum and strategy for empowering agricultural human resources institutions that greatly affect the availability and ease of access to innovative technology and information according to the needs of the actors involved. Using a qualitative descriptive method, this paper is a review of the results of the author's studies which aims to present the application of location-specific rice farming technology that is innovative and capable of being implemented by the producer farmers. This paper is enriched by citing several literatures, studies and other related articles. The occurrence of various changes and a decrease in people's income during and after the Covid-19 pandemic caused a decrease in purchasing power and access to food, which if sustained is predicted to result in instability and even food insecurity. Availability of active, pro-active policy instruments, and proper functioning of various supporting institutions (research, counseling, marketing), as well as government policy support that is more focused and impartial to accelerate the achievement of location-specific technological innovations. Continuous monitoring, evaluation and assistance is needed, implementation of location-specific agricultural development policy programs from the aspect of food institutions, so that strategies and policy formulation are accurate as an effort to support increasing national rice production in the future.